Integrasi Hak Kekayaan Intelektual dalam Tanggung Jawab Sosial Perusahaan di Era Ekonomi Kreatif - Putu Tirta Megawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study examines the integration of Intellectual Property Rights (IPR) into Corporate Social Responsibility (CSR) as a strategic legal instrument to support the development of the creative economy in Indonesia. The creative economy has become one of the main drivers of national economic growth; however, its development is often constrained by weak legal protection of intellectual property, particularly among micro, small, and medium enterprises. This research employs normative legal research using statutory and conceptual approaches. The findings indicate that the integration of IPR into CSR programs plays a significant role in enhancing legal awareness, strengthening protection of creative works, and promoting sustainable economic empowerment for communities. CSR-based IPR protection not only benefits right holders but also contributes to inclusive development and corporate sustainability. Therefore, strengthening CSR policies oriented toward IPR protection is essential to ensure balanced economic growth and legal certainty in the creative economy sector.